Modelling of cost of mechanical & electrical services between residential & commercial building projects using selected building form descriptors : A case study of selected building projects in Abuja and Niger State,Nigeria - Shittu .A.A,; Izam .Y.D, (Penerbit UKM, 2011)
This research was carried out to study the problem of ineffective cost control technique in the process of formulating predictive models for cost of Mechanical and Electrical (M&E) services due to the use of inadequate information to estimate cost of M&E services during the pre-contract stage of building projects which results in to cost overrun. The study also examined the cost relationship between M&E services and design variables which make up building forms, for residential and commercial building projects. The relationship between the variables in the data collected was examined with the use of simple and multiple regression analyses, correlation analysis and descriptive Statistics. One of the major findings of the research was that the cost of M&E services of any given residential or commercial building projects can be accessed from the building form descriptors with 95% confidence limits. This also provided a basis for developing several predictive regression models for M&E services cost for both residential and commercial building projects. Recommendations from the study included regular review of the models in the light of changing environmental circumstances by any user of the models, for the models to stand a test of time.